Edukasi Thoharoh Tentang Tata Cara Menghilangkan Najis Kepada Siswa TPQ Nurul Hidayah Dusun Mulyorejo - Habibi, Wildan; Sariroh, Maslahatus (LP3M IAIFA Kediri, 2022)
In islamic teachings, sanctification or thaharah becomes a very important role in worship. Not only in the case of prayer, the sanctity of self, body, clothing, and place Especially sanctifying which is related to the ordinance of removing uncleanness. Sanctification greatly affects the person's worship. That way, the purpose of worship is perfectly fulfilled. A slight mistake in sanctification will be fatal to worship, instead of getting a reward, it is sin that is obtained. Therefore, Islam pays great attention to the problem of purification, because purifying can make one's worship invalid. In the study itself, the author chose to use the PAR (Participatory Action Research) method. The results of this study, performed several steps as follows; The first step we take is to prepare the material that we will deliver. The first step we take is to prepare the material that we will deliver. The second step is that flexible methods and approaches are needed according to the circumstances. Because, there is often a gap between plans and practices in the field. The third step is to evaluate the education that has been carried out from beginning to end to children. This is an attempt to find out the extent of the material that has been captured by children during education.